Comparation of differences in the performance of corporate social responsibility between Chinese and American pharmaceutical enterprises—based on corporate social responsibility report - Xu, HongHao; Zhang, Meng; Chu, ShuZhen (Frontiers in Pharmacology, 2023)
OBJECTIVE: We compared Chinese and American pharmaceutical companies’ corporate social responsibility (CSR) reports to determine their differences and to analyze the possible reasons for them. METHODS: We took as a model the top 500 pharmaceutical companies from Torreya’s (a global investment bank) list of the 1000 most valuable pharmaceutical companies in the world. We then collected the 2020 CSR reports of 97 Chinese and 94 American pharmaceutical companies. These reports were analyzed using software such as ROST Content Mining 6.0 and Gephi 0.92. RESULTS: We formed a high-frequency word list, a semantic network diagram, and a high-frequency word centrality scale for the Chinese and American pharmaceutical CSR reports. The Chinese pharmaceutical companies’ CSR reports formed a layout of “double centers and double themes,” and the text paid more attention to the disclosure of environmental protection information. The American pharmaceutical companies formed a report presentation form of “three centers and two themes,” focusing on CSR information disclosures from the perspective of humanistic care. DISCUSSION: The differences in between Chinese and American pharmaceutical companies’ CSR reports may be due to different corporate development strategies, regulatory requirements, social demands, and the concept of “corporate citizenship.” This study makes recommendations for Chinese pharmaceutical companies to better fulfill their CSR at three levels: policy-making, company management, and society.